Distribution of haematological indices among subjects with Blastocystis hominis infection compared to controls - Javaherizadeh, Hazhir; Khademvatan, Shahram; Soltani, Shahrzad; Torabizadeh, Mehdi; Yousefi, Elham (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction : Some studies suggest Blastocystis hominis is a potentially pathogenic protozoa. Blastocystis hominis contributed to anaemia in children aged 8–10 years old in one study. Aim: To compare haematological indices in cases with Blastocystis hominis infection with healthy controls. Material and methods: From 2001 to 2012, 97600 stool examinations were done in 4 university hospitals. Parasites were observed in 46,200 specimens. Of these cases, subjects with complete laboratory investigation (complete blood count – CBC, ferritin, total iron binding capacity – TIBC, and serum) and Blastocystis hominis infection were included in this study as the case group. Of these cases, 6851 cases had only B. hominis infection. In the control group, 3615 subjects without parasite infestation were included. Age, haemoglobin (Hb), serum iron, TIBC, white blood cell (WBC), platelet (PLT), mean corpuscular volume (MCV), haematocrit (HCT) and erythrocyte sedimentation rate (ESR) were recorded for cases and controls. SPSS software version 13.0 was used for analysis. Independent sample t-test and 2 tests were used for comparison. Results: Erythrocyte sedimentation rate level was significantly higher in cases with B. hominis infection (p < 0.05). C-reactive protein level was positive in 1.46% of cases and 0.5% of controls, which was statistically significant (p < 0.05). Frequency of serum iron < 120 was significantly higher in cases with B. hominis infection compared to controls. Occult blood was positive in 0.93% of cases and in none of the controls (p < 0.05). Conclusions : The ESR, CRP and occult blood was significantly higher in cases with B. hominis infection.